По щучьему велению и другие сказки: сборник / худож. Н. Субочева - Субочева Н. (Путешествие в сказку, 2005)
Экземпляры: ф-21 (20210705) / Инвентарный номер: 57239 / Цена: 70.00 / Сис.шифр: Д / Авт.знак: П41 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)-6